“Life because of Righteousness” - Starling, David (2016)
This paper commences with an outline of the vision of the missio Dei that Paul offers to his readers in Rome, taking as a starting point the letter’s thesis statement in 1:16–17. The remainder of the paper traces the key pneumatological themes of the letter and orients them in relation to this overarching vision. The picture that emerges is one that highlights the close connectedness between the Spirit’s life-giving work and the saving righteousness manifested in Christ, proclaimed in the gospel, and at work within the church. Life without righteousness and righteousness without life are both, for Paul, equally unthinkable.
Keywords: Missio Dei -- Romans -- pneumatology -- Spirit -- mission -- righteousness